A review on the use of neem (Azadirachta indica) and its efficacy as an antiparasitic agent against ectoparasites affecting cattle - Haikal Nooruddin,
Ticks are the most important vectors of infectious diseases in domestic and wild animals. Tick worry, injection of toxins, hide damage, anemia, and reduced productivity are among the effects of tick infestation. Tick control programs rely heavily on the use of synthetic acaricides. This has led to several concerns with the major one being development of acaricide resistance. The exploitation of plants and plant products are believed to be a promising alternative since a long time ago. The traditional use of Azadirachta indica or neem as a control of tick vectors have been reported in tropical countries. This may suggest its efficacy against ticks. The objective of this study is to review the potential of using neem (4zadirachta indica) as an antiparasitic agent and its efficacy against tick vectors affecting cattle. Here, we reviewed relevant information published, focused on neem as repellents and acaricides against tick vectors with special interest to Rhipicephalus microplus, as this tick is known to be the most important tick parasite of cattle, and it is a vector for economically significant diseases. Neem extracts are found to have effects such as tick and larvae mortality alongside reducing reproductive parameters. Several factors play a role in its efficacy namely dose, concentration, and component of neem. However, there is lack of studies regarding the practical use of neem as a tickicide since most studies are conducted in vitro which may not truly reflect its effectiveness in field.